IDENTITY AND MOTIF OF COSPLAYERS SURABAYA IN ‘MATSURI NO KAMI’ EVENT - Amoynindi Dewanti Ardilla; Nabila Hani Apriliana; Felicia Meila Harijanto; Muizzu Nurhadi (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
The cosplay phenomenon has become increasingly widespread and growing with technological advances and people's thinking that is getting smarter in expressing themselves. Cosplay usually describes dressing and acting as characters from manga, anime, tokusatsu, video games, sci-fi and musical groups. Cosplay activities are unique by doing role-plays or character roles. In Indonesia itself, cosplay can be found at various cosplayer's events with the aim of appreciating their talents and hobbies. One of them is at the Royal Plaza, Surabaya in the context of the "Matsuri no Kami" event. This study uses a qualitative method by applying ethnography in which this research involves a description of humans and the nature of phenomena. As in the cosplay cast and the motifs of the cosplayers. This ethnographic research involves observation, interviews and data collection from sources. The results of the study show an explanation of the identity, motives, challenges to the benefits of cosplay for cosplayers.